Activation Studies of the γ-Carbonic Anhydrases from the Antarctic Marine Bacteria Pseudoalteromonas haloplanktis and Colwellia psychrerythraea with Amino Acids and Amines - Andrea Angeli; Sonia Del Prete; Sameh M. Osman; Zeid AlOthman; William A. Donald; Clemente Capasso; Claudiu T. Supuran (Marine Drugs, 2019)
The γ-carbonic anhydrases (CAs, EC 4.2.1.1) present in the Antarctic marine bacteria Pseudoalteromonas haloplanktis and Colwellia psychrerythraea, herein referred to as PhaCA and CpsCA, respectively, were investigated for their activation with a panel of 24 amino acids and amines. Both bacteria are considered Antarctic models for the investigation of photosynthetic and metabolic pathways in organisms adapted to live in cold seawater. PhaCA was much more sensitive to activation by these compounds compared to the genetically related enzyme CpsCA. The most effective PhaCA activators were d-Phe, l-/d-DOPA, l-Tyr and 2-pyridyl-methylamine, with the activation constant KA values of 0.72–3.27 µM. d-His, l-Trp, d-Tyr, histamine, dopamine, serotonin anddicarboxylic amino acids were also effective activators of PhaCA, with KA values of 6.48–9.85 µM. CpsCA was activated by d-Phe, d-DOPA, l-Trp, l-/d-Tyr, 4-amino-l-Phe, histamine, 2-pyridyl-methylamine and l-/d-Glu with KA values of 11.2–24.4 µM. The most effective CpsCA activator was l-DOPA (KA of 4.79 µM). Given that modulators of CAs from Antarctic bacteria have not been identified and investigated in detail for their metabolic roles to date, this research sheds some light on these poorly understood processes.